2017
DOI: 10.1007/s10439-017-1836-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineered Human Amniotic Membrane Application in Mouse Ovarian Follicular Culture

Abstract: Since folliculogenesis requires a powerful cell-matrix interaction, natural scaffolds seem to be needed for follicular culture. Human amniotic membrane (HAM) offers promise as a support of in vitro ovarian follicular culture. HAM was decellularized with trypsin and EDTA. DNA and histology assays were performed to determine the elimination rate of genomic components. Cyto-biocompatibility of decellular AM (DAM) was verified by the cell viability (MTT) test. The small parts of intact amniotic membrane (IAM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…In particular, acellular amniotic membrane was investigated as a scaffold to support/deliver epithelial cells [240], limbal stem cells [296], human adipose stem cells [297], differentiated neural-like cells [298], mice ovarian follicular culture [299], as well as a scaffold with cell-guiding ability [300] but it may also be used as a surgical patch/mesh [301] for reconstruction of vessels [302] (also once rolled up [303,304]); bladder [305] or circumferential urethral defect [306], reconstruction of esophageal wall [307], cardiac [120,308] and cerebrospinal fluid [308] applications, endometrial fibrosis treatment [309], soft tissue damage, limbal stem cell deficiency [293], skin defects also due to ulcers or severe skin burns or for corneal defects [310,311,312], treatment of pharyngocutaneous fistula after total laryngectomy [291], and for fetoscopic closure of iatrogenic defects in fetal membranes [313].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, acellular amniotic membrane was investigated as a scaffold to support/deliver epithelial cells [240], limbal stem cells [296], human adipose stem cells [297], differentiated neural-like cells [298], mice ovarian follicular culture [299], as well as a scaffold with cell-guiding ability [300] but it may also be used as a surgical patch/mesh [301] for reconstruction of vessels [302] (also once rolled up [303,304]); bladder [305] or circumferential urethral defect [306], reconstruction of esophageal wall [307], cardiac [120,308] and cerebrospinal fluid [308] applications, endometrial fibrosis treatment [309], soft tissue damage, limbal stem cell deficiency [293], skin defects also due to ulcers or severe skin burns or for corneal defects [310,311,312], treatment of pharyngocutaneous fistula after total laryngectomy [291], and for fetoscopic closure of iatrogenic defects in fetal membranes [313].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
“…Several decellularization methods were approached, often combining multiple phases based on physical (freezing–thawing), osmotic-chemical (Triton X-100, SDS, EDTA, Tris, NaOH, NH 4 Cl) and/or enzymatic (trypsin, dispase, lipase, DNase, and RNase) treatments [120,234,289,291,292,293,294,296,297,298,299,300,301,302,303,304,305,306,307,308,309,311,312,313,314,315,317,318,319].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The largest area of interest to emerge in the field of REPROTEN has been fertility restoration in female patients, as indicated by the numerous papers on the subject in this special issue, mainly focusing on ovarian tissue engineering. Studies by our group 2,20 and Motamed et al 14 have demonstrated that different scaffolds, using materials like fibrin, alginate and amniotic membranes, can be successfully applied to grow isolated preantral follicles. He 9 and David et al 5 developed exciting new strategies to encapsulate isolated follicles or fragments of ovarian tissue for further in vitro culture or transplantation to restore fertility or endocrine function.…”
mentioning
confidence: 98%
“…conditioned media are other techniques that are being investigated for better in vivo development of follicles. 6,[9][10][11] Many studies have used different synthetic (such as poly ethylene glycol 12 and polyvinyl alcohol 13 ), and natural matrices (such as agar, alginate, 14 derivation of hyaluronan, 15 and fibrin 16 ), as well as tissuederived extracellular matrix (ECM) (such as amniotic membranes 17 ) for in vitro culture of follicles. Synthetic matrices have limitations in terms of their biomechanical properties and are associated with high production costs.…”
mentioning
confidence: 99%